DIDACTIC OPPORTUNITIES FOR MODERNIZING THE MECHANISMS OF DEVELOPING PROFESSIONAL COMPETENCIES OF FUTURE PRESCHOOL EDUCATION TEACHERS BASED ON GAMIFICATION TECHNOLOGY - Xaydarova Namunaxon Adhamjonovna (International Scientific and Current Research Conferences, 2026)
This article analyzes the didactic opportunities for using gamification technology in the process of forming and developing the professional competencies of future preschool education teachers from scientific-theoretical and practical perspectives. In modernizing the educational process in accordance with the requirements of the competency-based approach, the integration of such components as motivation, activity orientation, reflection, assessment and cooperation on the basis of game mechanisms is explained as the main methodological solution. The article highlights the directions for modernizing the mechanisms of developing professional competencies through gamification, its didactic conditions and forms of practical implementation, such as mission, level, role situation, case, mini-project, rating and incentive model. The results of the study substantiate that a gamified educational environment is an effective didactic resource for the gradual development of future teachers’ methodological, communicative, psychological, creative and reflective competencies.